MODEL-MODEL PERKEMBANGAN PEMBELAJARAN BTQ DI TPQ/TPA DI INDONESIA - Kusuma, Yuanda (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Along with the development of the times, more and more alquran literacy needs. The demands of alquran's literacy skills have become one of the spreading phenomena. Therefore, there is a non-formal education institution which is usually called the Alquran Education Park. Al-quran education parks are almost in every area and have a variety of alquran literacy learning methods. These methods vary both from the principle, characteristics, methods and stages. So with the diversity of methods, TPQ institutions can adapt to the needs and characteristics of students, The diversity of these methods is also considered to be able to complement the deficiencies of the methods with each other. This paper seeks to describe the models for the development of BTQ learning in TPQ / TPA in Indonesia. . The results of this paper will, be insightful while discourse and early action to develop BTQ learning in Islamic education institutions.Keywords: al-Qur’an literacy; BTQ learning; al-Qur’an Education Park (TPQ)